2018
DOI: 10.1149/2.0031805jss
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Shear and Normal Force Trends in Tungsten Chemical Mechanical Planarization with Different Conditioning Discs

Abstract: In-situ conditioning is known to increase material removal rate (RR) during chemical mechanical planarization (CMP), because it roughens the pad surface that is in contact with the wafer. Previous studies have shown that the conditioning disc changes the pad surface micro-texture and affects the thermal, kinetic and tribological attributes of the CMP process. This study focuses on two different diamond discs for in-situ conditioning during tungsten CMP, and shows how real-time force data improves our understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…As seen in Fig. 4, a plot of directivity, 10,11 or , (defined as the ratio of measured variances in shear force to those of normal force) of all data points (regardless of ring or slurry types) vs. the pseudo-Sommerfeld number follow a common trend. It must be noted that a directivity value of unity indicates that the fluctuations in shear and normal force are identical.…”
Section: Tribological Studiesmentioning
confidence: 80%
“…As seen in Fig. 4, a plot of directivity, 10,11 or , (defined as the ratio of measured variances in shear force to those of normal force) of all data points (regardless of ring or slurry types) vs. the pseudo-Sommerfeld number follow a common trend. It must be noted that a directivity value of unity indicates that the fluctuations in shear and normal force are identical.…”
Section: Tribological Studiesmentioning
confidence: 80%
“…44 Directivity itself (taken from the science of characterizing old Italian violins, which believe it or not, have many similarities to CMP tools) [45][46][47][48][49][50] is defined as the ratio of measured variances in shear force to variances of normal force at a given polishing PV condition. 44,[51][52][53][54][55] Here, the fluctuating components of shear and normal forces are the key factors and not their absolute values. In this case, the ordinate and the abscissa are independent of one another, and because we use linear scales, there are no distortions or optical illusions that would have been caused by the logarithmic scales.…”
Section: Parametersmentioning
confidence: 99%
“…(13,14) Peckler et al also observed that Δ was affected by a CMP consumable, this time being the pad conditioner. (15) Separately, Peckler et al found that Δ somewhat increased with P × v and found a loose correlation between Δ and copper RR. (16) Mariscal et al also found a correlation between Δ and RR, but for a tungsten CMP application.…”
Section: Introductionmentioning
confidence: 99%
“…(12)(13)(14)(15)(16)(17) Previous work has focused on the vibrations that occur in various CMP processes. (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) Fukuroda et al, Hetherington et al, Kojima et al and Rao et al studied vibrations in CMP and found that they could be used as an end-point detection technique for polishing different materials. (18)(19)(20)(21) However, the authors did not correlate the vibrations to RR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation